Предмет: Алгебра,
автор: Napisat05
1)(b+6)(b-6)-3(b+2)
2)(3a-2)(3a+2)+(a-8)(a+8)
3)(5x-3y)(5x+3y)+(3x-5y)(3x+5y)
4)(c-2)(3-c)-(5-c)(5+c)
Ответы
Автор ответа:
0
(b + 6)(b - 6) - 3(b + 2) = b² - 36 - 3b - 6 = b² - 3b - 42
(3a - 2)(3a + 2) + (a - 8)(a + 8) = 9a² - 4 + a² - 64 = 10a² - 68
(5x - 3y)(5x + 3y) + (3x - 5y)(3x + 5y) = 25x² - 9y² + 9x² - 25y² = 34x² - 34y²
(c - 2)(3 - c) - (5 - c)(5 + c) = 3c - 6 - c² + 2c - 25 + c² = 5c - 31
(3a - 2)(3a + 2) + (a - 8)(a + 8) = 9a² - 4 + a² - 64 = 10a² - 68
(5x - 3y)(5x + 3y) + (3x - 5y)(3x + 5y) = 25x² - 9y² + 9x² - 25y² = 34x² - 34y²
(c - 2)(3 - c) - (5 - c)(5 + c) = 3c - 6 - c² + 2c - 25 + c² = 5c - 31
Похожие вопросы
Предмет: Английский язык,
автор: 20101014
Предмет: Физика,
автор: shamaniman
Предмет: Математика,
автор: artemamidov755
Предмет: Математика,
автор: Аноним